Peran Kelompok Tani Dwi Sejati Dalam Mensejahterakan Petani Padi Desa Banjarrejo Kecamatan Batanghari Lampung Timur - Dina Tri Mulyani; Hendri Stiawan; Khoirun Nisa; Carmidah Carmidah (Pusat Riset dan Inovasi Nasional, 2023)
Agriculture is a source of life and a source of income for people who work as farmers. In addition, farmer groups also have an important role in managing agriculture. Farmer groups can help the welfare of farmers with the programs they have. In this study using qualitative research to collect data through interviews with informants. The results of the study show that the Dwi Sejati farmer group plays an important role for rice farmers in Banjarrejo village, and can make it easier for farmers to manage agriculture.